Determinants of entrepreneurial career intentions: a case of undergraduate students at UNIKL (MIMET) Seri Manjung, Perak / Zakiah Mohamed and Hayati Abdul Jalal - Mohamed, Zakiah; Abdul Jalal, Hayati (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2017)
This paper explores determinants (i.e. personality traits of entrepreneurial innovativeness, entrepreneurial knowledge and entrepreneurial environment) contributing to the entrepreneurial career intentions among undergraduate students in UNIKL (MIMET) in Seri Manjung Perak. A survey was carried out with 300 respondents. Five-point Likert scales of 40 questionnaire items were developed to measure the constructs. Based on 209 completed data, both descriptive and inferential statistic was run. This study discovered that more than 70 per cent of the respondents have favourable attitude towards entrepreneurship. From the hierarchical multiple regression analysis, entrepreneurial knowledge and entrepreneurial environment have significant influence on entrepreneurial career intentions. Entrepreneurial environment was the most important predictor to entrepreneurial career intentions, followed by entrepreneurial knowledge. Entrepreneurial innovativeness had no significant relationship with entrepreneurial career intentions. These findings will be a value addition in Malaysia scenario and are likely to help Malaysian government in evaluating the success implementation of entrepreneurship program among undergraduates. Lessons and implications for entrepreneurship in Malaysian context are presented.